Fabrication, design and performance evaluation of supercapacitors review. (2022) - Mone, Parashar; Deore, Sawata; Balgude, Sagar; Pandit, Vikram
Abstract: Numerous research projects on various energy storage materials have been reported and are presently ongoing. Electrochemical supercapacitors (ESs) are one of the most researched types of energy storage devices. Because of globalization and the growing demand for smart and flexible devices, current research was focused on developing stable ESs that are low-cost and high-energy density. The fundamentals of the electrochemical supercapacitor based on interfacial capacitance, as well as superficial redox processes at the electrode/solution interface, are briefly addressed in this respect. The capacity of electrochemical double layers, charge storage electrode materials for supercapacitors, and supercapacitors was determined using experimental methods.